Student Academic Fraud during Maths Exams During the Covid-19 Pandemic Based on GONE Theory Dimensions - Sutrisno Sutrisno; Roro Qothrin Nida; F. X. Didik Purwosetiyono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
This study aims to describe students' academic fraud during math exams during the Covid-19 pandemic based on the missing theory dimension regarding students' academic abilities. This research was conducted in class IX, a junior high school in Semarang. Six subjects were selected purposively, with high, moderate, and low academic ability, two students each. Data collection uses test scores, academic fraud scales, and interviews. The technique of checking the validity of the data is through triangulation of sources and methods. This study shows that students with high, moderate, and low academic abilities commit academic fraud when taking the same exam but with different intensities. The background of the fraud is greed, opportunity, need, and exposure. The form of fraud is copying answers on the internet or collaborating with other friends while doing exams. Students do this because of the effects of online learning and the lack of supervision from the teacher during the exam.